World War I the definitive visual history: from Sarajevo to Versailles - Grant, R. G. (Dorling Kindersley Limited, 2018)
A guide to the first World War features timelines, maps, and accounts of the action to bring to life the world leaders, key players, and soldiers who fought the battles with weapons and new technologies that changed history